An alternative powerful approach to multiple hypotheses testing: Application in a correlation study - Stapor, Katarzyna; Kończak, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
The multiple hypothesis testing problem occurs when a number of individual hypothesis tests are considered simultaneously. The larger the number of inferences (tests) made, the more likely erroneous inferences become. Several classical statistical techniques have been developed to address this problem. Unfortunately, very often, in studies that aim to examine the significance of multiple effects (for example, correlations), the effect of multiple testing is ignored. This leads to an inflated number of significant findings (e.g., correlation coefficients).
Keywords: multiple hypothesis testing; linear correlations; permutation tests